Cultural globalization a user's guide - Wise, J. Macgregor (John Macgregor) (Malden, MA : Blackwell, 2008)
Cultural Globalization: A User's Guide is a personal and engaging journey through theories of culture and globalization. Drawing on extensive examples and interdisciplinary research, Wise explores concepts of culture, territory and identity in order to give students a new perspective on issues of globalization. Includes numerous examples from Asian, European, and North American youth culture and popular music Draws on interdisciplinary research from the fields of anthropology, cultural studies, cultural geography, and media studies Considers how global processes carry with them the ethical questions of how to act in the world and how to care for others Provides an original and stimulating overview of theories of culture and globalization, encouraging students think more broadly about the key issues.
Ηλεκτρονικό βιβλίο
Keywords: Culture and globalization; Electronic books